2022
DOI: 10.3390/healthcare10071178
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Pain, Psychological Symptoms, and Diagnostic Struggles among Patients with Tick-Borne Diseases

Abstract: Public health reports contain limited information regarding the psychological and neurological symptoms of tick-borne diseases (TBDs). Employing a mixed-method approach, this analysis triangulates three sources of symptomology and provides a comparison of official public health information, case reports, and medical literature, and the self-reported symptoms of patients with Lyme disease and other TBDs. Out of the fifteen neuropsychiatric symptoms reported in the medical literature for common TBDs, headaches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 123 publications
(133 reference statements)
0
10
0
Order By: Relevance
“…Six (6) bacterial OTUs were (≥60%) identified to species level, these are Coxiella burnetii , Pseudomonas fluorescens , Proteus mirabilis , Staphylococcus agnetis , Corynebacterium ulcerans and Cutibacterium acnes (Table 3). Cytochrome Oxidase I sequence data improved the resolution in identification of bacteria that use oxidative phosphorylation such as Coxiella and Rickettsia .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six (6) bacterial OTUs were (≥60%) identified to species level, these are Coxiella burnetii , Pseudomonas fluorescens , Proteus mirabilis , Staphylococcus agnetis , Corynebacterium ulcerans and Cutibacterium acnes (Table 3). Cytochrome Oxidase I sequence data improved the resolution in identification of bacteria that use oxidative phosphorylation such as Coxiella and Rickettsia .…”
Section: Resultsmentioning
confidence: 99%
“…Among these diseases, tick-borne bacterial infections like Lyme disease, anaplasmosis, ehrlichiosis, and rickettsiosis pose significant global health threats (5). These diseases not only cause debilitating symptoms but, if left untreated, can result in chronic health issues and fatalities, imposing a substantial burden on healthcare systems and compromising a country’s economy (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Public health reports provide limited information on the neuropsychiatric comorbidities of LD. Utilizing a mixed-method approach, Maxwell et al’s study triangulates three data sources to compare official public health information, case reports, and medical literature to self-reported symptoms in patients with LD [ 21 ]. Among the 15 neuropsychiatric symptoms documented in the medical literature for LD, Maxwell et al found that public health officials only fully recognized headaches and fatigue [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…LD symptoms and healthcare expenses can have broad implications for individual patients. For instance, LD-related sequelae may lead to socioeconomic effects through healthcare costs or missed work (Johnson et al, 2011 ; Hirsch et al, 2018 ; Schwartz et al, 2020 ; Maxwell et al, 2022 ). There also may be a disproportionate burden on low-income, uninsured, or under-insured individuals who do not have sick leave or lack the means to seek care (Hirsch et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%